2019
DOI: 10.1111/jcmm.14352
|View full text |Cite
|
Sign up to set email alerts
|

BAG3‐positive pancreatic stellate cells promote migration and invasion of pancreatic ductal adenocarcinoma

Abstract: BAG3 is constitutively expressed in multiple types of cancer cells and its high expression is associated with tumour progression and poor prognosis of PDAC . However, little is known about the role of BAG3 in the regulation of stromal microenvironment of PDAC. The current study demonstrated that beside PDAC tumour cells, BAG3 was also expressed in some activated stroma cells in PDAC tissue, as well as in activated PSCs. In addition, the current study demonstrated that BAG3 expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…The interaction between the tumor microenvironment and pancreatic cancer cells has been widely reported. 28 PSCs, which exist mainly in the forms of resting and activated cells, are one of the important cellular components in the stroma and the main progenitors of cancerassociated fibroblasts in pancreatic cancer. 29 Quiescent PSCs have the ability to store cytoplasmic lipids, which are usually present in connective tissue in small quantities, and secrete only a small amount of ECM components for the maintenance of normal tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the tumor microenvironment and pancreatic cancer cells has been widely reported. 28 PSCs, which exist mainly in the forms of resting and activated cells, are one of the important cellular components in the stroma and the main progenitors of cancerassociated fibroblasts in pancreatic cancer. 29 Quiescent PSCs have the ability to store cytoplasmic lipids, which are usually present in connective tissue in small quantities, and secrete only a small amount of ECM components for the maintenance of normal tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Yuan et al recently showed that the tumor stroma, pancreatic stellate cells, occasionally expresses high levels of BAG3. Using ectopic overexpression of BAG3 in vitro in pancreatic stellate cells, they could further exemplify that conditioned medium derived from these cells is capable to induce migration and invasion in PDAC cell lines and that this was mediated by expression and secretion of cytokines like IL-8, TGF-β2 and IGFBP2 [65].…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Bcl2-associated athanogene 3 (BAG3) is expressed by multiple cancer types, including PDAC, and correlates with poor prognosis. Recent studies show that this marker is also present in activated PSCs and may promote, via IL−6, TGF−β2, and insulin-like growth factor-binding protein 2 (IGFBP2) signaling, autocrine-driven maintenance of the activated phenotype in these cells (Yuan et al, 2019). Vice versa, BAG3−positive PSCs also increase migration and invasion capacity of nearby cancer cells via soluble factors such as IL−8, monocyte chemoattractant protein-1 (MCP-1), TGF−β2, and IGFBP2 (Yuan et al, 2019).…”
Section: Signaling In Psc-cancer Cell Interactionsmentioning
confidence: 99%
“…Recent studies show that this marker is also present in activated PSCs and may promote, via IL−6, TGF−β2, and insulin-like growth factor-binding protein 2 (IGFBP2) signaling, autocrine-driven maintenance of the activated phenotype in these cells (Yuan et al, 2019). Vice versa, BAG3−positive PSCs also increase migration and invasion capacity of nearby cancer cells via soluble factors such as IL−8, monocyte chemoattractant protein-1 (MCP-1), TGF−β2, and IGFBP2 (Yuan et al, 2019). A recent report shows that plasminogen activator inhibitor-1 (PAI-1), a common regulator of blood coagulation, cell apoptosis, and migration, is secreted by pancreatic cancer cells and activates PSCs LRP-1/ERK/c-JUN signaling (Wang et al, 2019).…”
Section: Signaling In Psc-cancer Cell Interactionsmentioning
confidence: 99%